The Influence of Service Quality and Work Discipline on Inpatient Satisfaction at Kabelota Donggala Regional Hospital - Izzah, Nurul; Natsir, Syahir; Hasanuddin, Bakri; Wirastuti, Wiri (Universitas Muhammadiyah Pontianak, 2025)
This study investigates the influence of service quality and work discipline on inpatient satisfaction at Kabelota Donggala Regional Hospital. Using a quantitative approach with a sample of 47 inpatients, data were collected through questionnaires and analyzed using multiple linear regression. The results indicate that both service quality and work discipline have a positive and significant impact on patient satisfaction, both partially and simultaneously. The findings highlight the importance of maintaining professional healthcare services to improve patient satisfaction and inform future strategies for hospital service enhancement.